The effect of cosmos caudatus kunth leaves on the mortality of aedes aegypti mosquitoes: A preliminary study - TJIPTO RINI (International Journal of Pharma and Bio Sciences, 2018)
Dengue fever, one of the dangerous diseases in Indonesia, is transmitted by Aedes aegypti mosquitoes as the main vector. Prevention of infectious diseases which are spread by particular vectors is possible only if the vectors are controlled. One of the vector control methods is using chemical substances. However, eradication of dengue fever using chemical substance has negative impacts. Hence, natural insecticide was introduced as vector control management option. Cosmos caudatus Kunth has a great potential as natural insecticide which contains saponin and essential oil. Saponin functions as a contact poison and gastric poison, whilst essential oil is toxic for insect respiratory system which leads to mortality. The aim of this research was to evaluate the effect of boiled Cosmos caudatus Kunth leaves on Aedes aegypti mosquitoes mortality. Study design was quasi experimental with sample of 480 (four hundred and eighty) Aedes aegypti mosquitoes, which were collected and analyzed at Entomology and Parasitology Laboratory, Environmental Health, Health Polytechnic Jakarta II Indonesia, in May 2016. Dependent variable was the number of Aedes aegypti mosquitoes mortality and independent variable was boiled Cosmos caudatus Kunth leaves. The result of the research was that the solution with 60% concentration level of boiled Cosmos caudatus Kunth leaves could kill one (1) mosquito, which is five percent (5%) of the total number of mosquitoes being tested. Whereas, the solution with 100% concentration level (undiluted) resulted in four (4) mortality or, in other words, twenty percent (20%) of the total number of mosquitoes which were tested. Effectiveness of boiled Cosmos caudatus Kunth leaves in eradicating insect was found low. Hence, an active ingredients acquisition technique such as extraction of Cosmos caudatus Kunth leaves is needed for further research.